2014
DOI: 10.1093/infdis/jiu225
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of Recent and Long-Term Malaria Transmission in a Population by Antibody Testing to Multiple Plasmodium falciparum Antigens

Abstract: Antibodies to P. falciparum antigens in malaria-endemic areas vary by age, antigen, and time since last exposure to P. falciparum. Multiplex P. falciparum antibody testing could provide estimates of long-term and recent malaria transmission and potentially of a population's susceptibility to future clinical malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 35 publications
7
62
0
Order By: Relevance
“…37 This was supported by recent data from another study in Nandi that suggests that the half-lives of MSP1 antibodies in older children and adults can be on the order of decades. 38 Our work is consistent with these findings, supporting the notion that antimalarial antibody titers could be used as a surrogate of past exposure history in children and a tool for monitoring malaria control programs. [39][40][41] Although we were underpowered to detect significant changes in cellular immune responses in most cases, some trends did emerge in our analysis.…”
Section: Discussionsupporting
confidence: 87%
“…37 This was supported by recent data from another study in Nandi that suggests that the half-lives of MSP1 antibodies in older children and adults can be on the order of decades. 38 Our work is consistent with these findings, supporting the notion that antimalarial antibody titers could be used as a surrogate of past exposure history in children and a tool for monitoring malaria control programs. [39][40][41] Although we were underpowered to detect significant changes in cellular immune responses in most cases, some trends did emerge in our analysis.…”
Section: Discussionsupporting
confidence: 87%
“…The P. falciparum antigens MSP-1 and AMA-1 have been used extensively in malaria serological studies, 11,[17][18][19][20] and are both thought to induce IgG antibody responses which would be present for long periods of time following infection. 10,21 For this cohort of Malian children, we found the MFI-bg signal intensities for each of these antigens to be highly skewed, with the distinct possibility of having a high titer for one of these antigens and not for the other (Figure 2). However, the antibody signal intensities for these two antigens were found to be correlated for the overall population of children (Spearman's rank correlation coefficient: ρ = 0.493, P < 0.0001).…”
Section: Resultsmentioning
confidence: 91%
“…Even though, limited information on the Abs persistence is available, some studies have previously estimated Ab half-lives [18, 20]. A study performed by Drakeley et al [40] found a very long half-life of 49.8 years for Abs against Pv.MSP1.19, and Ondigo et al [67] found half-lives from <1 year (3 Ags) to moderate (5–20 years for 3 Ags) and very long (>40 years for 5 Ags) by means of the threshold approach. Wipasa et al [18] and Fowkes et al [20] found a clearance of approximately 7.6 years [18] and 0.8–7.6 years [20], respectively, through linear regression models for the same Abs.…”
Section: Discussionmentioning
confidence: 99%